2017
DOI: 10.1038/s41598-017-03389-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from palmitic acid-treated hepatocytes induce fibrotic activation of hepatic stellate cells

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a dominant cause of chronic liver disease, but the exact mechanism of progression from simple steatosis to nonalcoholic steatohepatitis (NASH) remains unknown. Here, we investigated the role of exosomes in NAFLD progression. Exosomes were isolated from a human hepatoma cell line treated with palmitic acid (PA) and their miRNA profiles examined by microarray. The human hepatic stellate cell (HSC) line (LX-2) was then treated with exosome isolated from hepatocytes. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 44 publications
5
173
0
2
Order By: Relevance
“…Upregulation of CD36 expression increases fatty acid uptake resulting in excess lipid supply and subsequent lipid accumulation in lung and heart which can induce cardiac hypertrophy and contractile dysfunction. Studies have found that palmitic acid increases CD36 expression, and palmitoylation results in abnormal lipid accumulation in cells . Since we had a significant increase in circulating palmitate, the upregulation of CD36 may be a sequelae to the metabolite.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Upregulation of CD36 expression increases fatty acid uptake resulting in excess lipid supply and subsequent lipid accumulation in lung and heart which can induce cardiac hypertrophy and contractile dysfunction. Studies have found that palmitic acid increases CD36 expression, and palmitoylation results in abnormal lipid accumulation in cells . Since we had a significant increase in circulating palmitate, the upregulation of CD36 may be a sequelae to the metabolite.…”
Section: Discussionmentioning
confidence: 73%
“…Studies have found that palmitic acid increases CD36 expression, and palmitoylation results in abnormal lipid accumulation in cells. 31 Since we had a significant increase in circulating palmitate, the upregulation of CD36 may be a sequelae to the metabolite. In addition, we have found that the levels of 2-Octenoylcarnitine and 9-decenoylcarnitine were decreased in the CHD-PAH patients.…”
Section: Discussionmentioning
confidence: 90%
“…Saturation of hepatocytes with lipids in NASH contributes to the production of lipotoxic compounds and cell death due to mitochondrial dysfunction and ROS production [88]. Finally, the treatment of hepatocytes with palmitic acid does not only induce apoptosis but also enhances the ability of hepatocyte-derived exosomes to activate HSCs [89].…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Interestingly, exosomes isolated from adipose explants obtained from obese patients can enter primary hepatocytes in vitro and induce deregulation of the transforming growth factor β (TGFβ) pathway . On the other hand, EVs released by primary murine hepatocytes or HepG2 cells during a lipotoxic challenge with palmitic acid are internalized by hepatic stellate cells in vitro, resulting in efficiently transferred miRNAs, including miR‐128‐3p , miR‐122 and miR‐192 , and suppression of PPARγ, and activation of the expression of fibrotic genes . Moreover, repeated injection of exosome‐like particles released by hepatic immature myeloid cells from obese mice causes an accumulation of CD11b cells in the liver of the receptor mice, and these cells release pro‐inflammatory cytokines and induce natural killer T cell apoptosis .…”
Section: Exosomes and Evs In Diabetesmentioning
confidence: 99%